New sensibility in modern arabic prose (Philology, 2026)
This paper deals with the Arabic Prose of the 1960s and 1970s through an analysis of the novels by Najīb Maḥfūz, Mīkhāʼīl Nuʽayma, Yūsuf al-Qaʽīd and Imīl Ḥabībī who represent different countries, generations and schools of literature. In spite of their thematic and stylistic diversity, the authors are united by a new sensibility related to their common endeavor to get out of the frame of the external plausibility and the literary canons. Thereby, they are able to create a new everyday reality through the strengthening of the artistic convention and rethinking the archaic models in their works.
Keywords: renovation; sensibility; identity; antirealism; convention